ANALISIS GAYA BAHASAANTOLOGI PUISI “CATATAN PADA DAUN” OLEH L.K.ARA - Sahri Nova Yoga (AN-NAS, 2022)
This study aims to determine: (1) The style of language contained in the poem Notes on the Leaves, Medan Kotaku, Di Pintu Kampus Itu from the poetry anthology "Notes on the Leaves" by L.K. Ara. (2) The meaning contained in the poem Notes on the Leaves, Medan Kotaku, At the Gate of the Campus is from the poetry anthology "Notes on the Leaves" by L.K. Ara. This type of research is descriptive qualitative research which means the research does not use statistical analysis procedures or other quantification methods. The object of this research is a poetry anthology entitled "Notes on the Leaves" by L.K.Ara. The use of various language styles described by Keraf in the anthology of poetry "Notes on the Leaves" by L.K.Ara can be detailed as follows: (1) Language style based on word choice emphasizes more towards informal language styles; (2) The tone-based language style uses simple, noble, powerful and medium language styles; (3) The style of language based on sentence structure uses a periodic and balanced type of sentence structure; based on its structure, it uses a sentence structure which is a derivative of the periodic nature, as well as a parallelism sentence structure; and (4) language style based on whether or not the meaning of the anthology of poetry entitled “Notes on the Leaves” by L.K.Ara is made, hyperbole and personification are more common.